A revision of the new world stiletto fly genus Ataenogera Kröber (Diptera: Therevidae: Phycinae) with the description of two new species - Hauser, Martin; Webb, Donald W. (Zootaxa, 2007)
The New World genus Ataenogera Kröber is revised with all species illustrated and distribution maps provided along with a key to species. Ataenogera includes six species, two of which (Ataenogera argentifrons sp. nov. and A. irwini sp. nov.) are new to science. Ataenogera brevicornis (Bromley) is resurrected from synonymy with A. abdominalis Kröber and is considered a discrete species.